Critical Approaches in Nursing Theory and Nursing Research Implications for Nursing Practice - Foth, Thomas 1960-; Holmes, Dave 1967-; Hülsken-Giesler, Manfred 1966; Kreutzer, Susanne; Remmers, Hartmut 1952- (V&R Unipress, 2017)
This comprehensive collection offers a unique look at nursing practice, theory, research and nursing history from various critical theoretical perspectives. It aims to initiate an international discussion among scholars from diverse countries, particularly Germany and Anglo-American countries, coming from distinctive schools of thought, e.g. German Critical theory and Post-structural approaches, and influenced by their respective histories of sciences. This book analyzes and criticizes nursing theory, nursing research and practice along several dimensions: Nursing Ethics, Subjectivity, Body and Flesh (Leib), Technology, Power, History, and Education
Keywords: Geschichte; Kritische Theorie; Krankenpflege; Gesundheitspolitik